EN122 Engineering mechanics : comprehensive learning, a complete guide (a student workbook) for first year engineering students - Ales, S.K. Dr
A comprehensive and self-contained student workbook will help first year students of mechanical engineering to acquire understanding of fundamental concepts and applications of engineering mechanics.